ETNOBOTANI TANAMAN OBAT OLEH MASYARAKAT DAYAK BAKUMPAI DI DESA MUARA RIPUNG KECAMATAN DUSUN SELATAN KABUPATEN BARITO SELATAN PROVINSI KALIMANTAN TENGAH - Reynaldi Reynaldi; Adi Rahmadi; Henny Arryati (Universitas Lambung Mangkurat, 2020)
This study aims to find out what medicinal plants are used by the people of Dayak Bakumpai in Muara Ripung village, including how the community processes these plants into medicinal to treat diseases and which parts of the plant are used most as a treatment. the data was obtained by interviewing the village physician using snowball sampling technique. The results of this study of medicinal plants used consisted of 10 types of Green Algae (Caulepra racesmosa), Ketepeng Cina (Senna alata), Mengkudu (Morinda citrifolia), Langir (Albizia saponaria), Rotan (Calameae calamus), Banana (Musa acuminata), Bambu Kuning (Bambusa vulgaris), Kenanga (Cananga odorata), Simpur (Dillenia exelsa), and Daun Seribu (Achillea millefolium). How to cultivate these plants with a variety of ways such as mashed, boiled, baked, soaked, dried and etc.Keywords: Ethnobotany, Medicinal Plants, Dayak Bakumpai